Sports Motivation Survey And Physical Activity Students Of Sport Education Teacher Training And Education Faculty FKIP Muhammadiyah University Surakarta - Gatot Jariono; Nur Subekti (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study reveals the motivation to exercise and physical activity of UMS POR students in the COVID 19 new order. This study aims to explore the perceptions, strategies, and challenges of UMS POR students in the COVID 19 new order in having the motivation to exercise and perform physical activities during the Covid-19 pandemic. This case study uses quantitative and qualitative methods. Quantitative data using questionnaires and qualitative data obtained through interactive interviews using google forms. Quantitative data were analyzed using descriptive statistics of frequencies through Excel Microsoft 2013 and qualitative data were analyzed through interactive thematic data analysis. The results showed that (i) the sports motivation of UMS POR students in the COVID 19 new order was in a good category or 61.21%, (ii) The physical activity of UMS POR students in the COVID 19 new order was in a good category or was 71.03%. This study recommends that the more frequent physical activity students maintain their physical quality, this must be balanced with sports motivation that is qualified in the COVID 19 new order.